Hubungan Pengetahuan dan Pendapatan Keluarga dengan Kejadian Stunting pada Balita di Puskesmas Rantau Selamat Aceh Timur Tahun 2024 - Dina Saputri; Ester Simanullang (Lembaga Pengembangan Kinerja Dosen, 2025)
The incidence of stunting in toddlers is one of the global nutritional problems. Based on UNICEF data from 2010–2017, it shows that the prevalence of stunting in the world reached 28%, in Eastern and Southern Africa it was 40%, and in South Asia it was 38%. When compared with the